2021
DOI: 10.1007/978-981-16-6506-6_2
|View full text |Cite
|
Sign up to set email alerts
|

The Problem with Universities Today

Abstract: Managerialism creates burdens for academics with no evidence for its benefit. Business imperatives override educational. There is needless competition between universities. Research imperatives override education. Global inequalities in educational need are ignored, universities have not kept up with the way young people gain information and initiatives to reduce the environmental impact of higher education are ‘tinkering’ rather than the required total re-thinking of higher education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This brings us to the third fact: it was concluded that there is no conflict coordination mechanism to promote goal integration at the organisational level in university organisations. Heller (2021) points out that universities adopt managerialism uncritically, but there is no evidence that this approach is beneficial. The above results also show that it is difficult to expect organisational change toward autonomous managerial capabilities by strengthening managerialism.…”
Section: Discussionmentioning
confidence: 99%
“…This brings us to the third fact: it was concluded that there is no conflict coordination mechanism to promote goal integration at the organisational level in university organisations. Heller (2021) points out that universities adopt managerialism uncritically, but there is no evidence that this approach is beneficial. The above results also show that it is difficult to expect organisational change toward autonomous managerial capabilities by strengthening managerialism.…”
Section: Discussionmentioning
confidence: 99%
“…There remain many regional and global inequalities in access to higher education. 39 As an illustration, by the year 2050, a quarter of the world's population will be African, 40 and there is a global responsibility to assist in the educational needs that this growth represents. Providing educational materials and processes through open access to them has the potential to help address inequity in access to higher education.…”
Section: Is There Really a Need For Plan E?mentioning
confidence: 99%
“…This would allow the publication of education output to be included in the university metrics -considered to be one of the reasons that universities currently value research over teaching, which exacerbates the teaching/research divide within universities. 46 Plan E might thus even have the collateral benefit of increasing the way teachers are valued in the higher education sector.…”
Section: Overcoming Policy Objectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, concepts like academic resilience emerged and, majority of the brick and mortar-based schools and higher education institutions tried their level best to be functional via only online means attempted to remain functionally open using online means. The academia took up to challenges in robust ways, and ensured the human machinery and the connected stakeholders be agile and adaptive for walking the path in new ways (15).…”
Section: Introductionmentioning
confidence: 99%